Mapping History; Surveying the Unfathomable in Pynchon’s Mason & Dix - Marwan Maho Abdi; Sherzad Shafie Babo (Zanco Journal of Humanity Sciences)
This article examines Thomas Pynchon's Mason and Dixon, as a leading example of historiographical metafiction which seamlessly blends fictional narratives with factual elements. This novel explores the relationship between geography and parageography, and emphasizes the relationship between cartography and storytelling. By exploring the power dynamics which are inherent in mapmaking and storytelling, the paper examines how mapmaking and the inscription of history assist imperial authorities to impose and perpetuate their dominance over others. Through a close examination of Pynchon's non-linear and complex narrative structure, this article highlights the manners in which Mason & Dixon counters the conventional notions of truth, hence inviting the reader to question any constructed nature either, maps or historical representation. Ultimately, this metafictional narrative prompt deeper investigation of the intricate intersections between fiction, historiography, geography, and the manipulation of knowledge.